Les notices d’autorité en XML-TEI : un outil pour l’accroissement collaboratif de connaissances et l’indexation d’éditions de sources - Marie Bisson; Anne Goloubkoff (Tabularia)
This article presents a tool designed at the pôle Document numérique of the Maison de la Recherche en Sciences Humaines of the University of Caen Normandie. Its goal is, on one hand, to foster the creation and cross enrichment of thesaurus (an XML database) based on information collected through texts and, on the other hand, to provide a fine indexing of the information found in texts. This tool is collaborative: it allows any researcher working on different editions of sources to enrich a shared XML database. The context of inception of this tool was about publishing old sources, meaning scientific publishing with research and data analysis objectives, but still considering the objectives of material publishing, with the capability of publishing the output of the research work.